Chemical, structural and mechanical characterization of bovine enamel. (January 2020) - Arango-Santander, Santiago; Montoya, Carolina; Pelaez-Vargas, Alejandro; Ossa, E. Alexander
Highlights: Bovine and human enamel are similar in composition and structure. Human and bovine enamels show similar hardness. Bovine enamel has higher fracture toughness than human enamel. Abstract: Objective: The purpose of this investigation was to establish microstructure, microhardness, fracture toughness, chemical composition, and crack repair of bovine enamel and to compare these features with their human counterparts. Design: Bovine enamel fragments were prepared and optical microscopy and atomic force microscopy were used to establish microstructure; Raman spectroscopy was used to estimate composition and microindentation using Vickers testing was performed to evaluate hardness. Results: A strong dependence between indentation load and microhardness values was observed, as was the case in human enamel. Similar microstructure and chemical composition between bovine and human enamel, 7.89% lower microhardness and 40% higher fracture toughness values for bovine enamel were found. Conclusion: From a structural and mechanical standpoint, bovine enamel is a suitable alternative to human enamel for in vitro testing of dental products.